Copper and zinc in commonly consumed bivalves from Pantai Remis Jeram, Selangor, Malaysia - Udechukwu, Bede Emeka; Ahmad Ismail, (University Kebangsaan Malaysia, 2013)
Four commonly consumed bivalves in Pantai Remis Jeram, Selangor, were evaluated for heavy metals concentration. Bivalve species were included cockle (Anadara granosa), clams (Pholas orientalis, Fragnum unedo and Donax faba), which are locally known as kerang, mentarang, kepah and lala respectively. The purpose of this study was to provide basis information on the concentrations of potentially harmful heavy metals (Cu and Zn) in commercialized seafood samples from Pantai Remis Jeram, Selangor. Metals concentration were determined using air- acetylene Perkin ElmerTM flame atomic absorption spectrophotometer (AAS), model A Analyst 800. Data was analyzed using SPSS 17 software for ANOVA test, and Post Hoc Test (Turkey HSD, p < 0.05).The maximum Cu and Zn concentrations in these bivalve samples were (20.42 ± 0.73 μg/g dry weight) (mentarang) and (906.57 ± 0.65 μg/g dry weight) (kerang) respectively. A significant (P < 0.05) high level of zinc was found in cockle, though not exceeding the maximum permissible limit set by Malaysia Food Regulation.